(untitled) (SCIENCE TIME JOURNAL, 2026)
This article investigates the poetic interpretation of the «Motherland» concept in the qasida «O‘zbegim» by Uzbek poet Erkin Vohidov and the poem «England, My England» by English poet William Ernest Henley through a comparative linguostylistic and linguocultural lens. The study analyzes the lexical-semantic, figurative-metaphorical, and axiological layers of both works. The findings show that both poets exalt the Motherland as a symbol of national pride, historical memory, and loyalty. However, Erkin Vohidov’s imagery is centered on mother, land, people, and national identity, while Henley’s poem links the Motherland to the English national spirit, heroism, imperial historical legacy, and the idea of freedom. The study reveals the linguocultural specificity of the Motherland concept in poetic texts.